2001
DOI: 10.1523/jneurosci.21-18-07063.2001
|View full text |Cite
|
Sign up to set email alerts
|

Secretin Facilitates GABA Transmission in the Cerebellum

Abstract: Secretin was the first hormone discovered in human history, and yet, its function as a neuropeptide has been overlooked in the past. The recent discovery of the potential use of secretin in treating autistic patients, together with the conflicting reports on its effectiveness, urges an in-depth investigation of this issue. We show here that in the rat cerebellar cortex, mRNAs encoding secretin are localized in the Purkinje cells, whereas those of its receptor are found in both Purkinje cells and GABAergic inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
93
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(104 citation statements)
references
References 40 publications
(42 reference statements)
11
93
0
Order By: Relevance
“…This is the first time that SCT expression has been manipulated in specific cells and hence provides a more powerful model to investigate the exact function of SCT in specific cells. In WT mice, SCT was strongly expressed in the soma and dendrites of Purkinje cells (Figures 1b and d), consistent with results obtained from a previous rat cerebellum study (Yung et al, 2001). In Pur-Sct À / À mice, SCT was still expressed in the deep cerebellar nuclei, hippocampus, and hypothalamus (Figures 1f-i) as previously described (Ng et al, 2002), confirming the Purkinjespecific knockout of SCT.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…This is the first time that SCT expression has been manipulated in specific cells and hence provides a more powerful model to investigate the exact function of SCT in specific cells. In WT mice, SCT was strongly expressed in the soma and dendrites of Purkinje cells (Figures 1b and d), consistent with results obtained from a previous rat cerebellum study (Yung et al, 2001). In Pur-Sct À / À mice, SCT was still expressed in the deep cerebellar nuclei, hippocampus, and hypothalamus (Figures 1f-i) as previously described (Ng et al, 2002), confirming the Purkinjespecific knockout of SCT.…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, rotarod motor latencies for Sct À / À , Sctr À / À , and Pur-Sct À / À mice increased slightly after repeated trials (Figures 3c and d), illustrating motor learning deficits. The abnormal behavioral phenotypes that we discovered, combined with results from previous studies on the SCT-mediated potentiation of rat Purkinje cell IPSCs (Yung et al, 2001) and the specific knockout of SCT in Purkinje cells of the mouse model, strongly support the involvement of the SCT-SCTR axis in motor coordination and learning abilities through the modulation of Purkinje cell neural transmission.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Secretin has also been determined to be expressed in distinct neuronal populations within the cerebellum and cerebral cortex (Couvineau et al, 1986;Yung et al, 2001). It has also been reported that VIP, which is structurally similar to secretin, exhibited neurite-promoting effects in ventral spinal cord cells (Iwasaki et al, 2001).…”
Section: Discussionmentioning
confidence: 99%